Ayurvedic Treatment Protocol in the Management of Kapha Vataja Gridhrasi- A Case Report (International Journal of Ayurveda and Pharma Research, 2023)
The disease wherein the Kandara which passes through the Parshni (the region below Gulphabhaga) towards the Pratyanguli gets affected by Vata dosha resulting in difficulty in Prasarana of Sakthi (region starting from Gulpha and ending in Vitapa) is called Grdhrasi. Grdhrasi is of two types Vataja and Vatakaphaja, hence the factors that cause the vitiation of Kapha should also be considered in case of Vata kaphaja Grdhrasi. Patient was a 38 years old female Software engineer, complaints of severe low backache radiating to right lower limb which is continuous for last 3 weeks. Since 4 years she is under allopathic medication and she is getting only temporary relief. Since the patient was having Kapha vataja gridhrasi, along with Sama lakshana, Rukshana was the initial line of management, followed by Snigda sweda and Erandamooladi niruha basti. The case study suggested that an Avastha anusara ayurveda treatment will be effective in managing Kapha vataja gridhrasi. Ayurveda treatments can arrest the progress of the disease. Kaphavatahara treatments were adopted mainly focusing on Kapha. With a thorough understanding of Dosha involved we can manage the complex conditions like Gridhrasi.